Evolution Characteristics of Sand-Dust Weather Processes in China During 1961–2020 - Duan, Haixia; Hou, Wei; Wu, Hao; Feng, Taichen; Yan, Pengcheng (Frontiers in Environmental Science, 2022)
The spring sand-dust weather can be disastrous in China. It seriously endangers agricultural production, transportation, air quality, people’s lives and property, and is a subject of sustained and extensive concern. Currently, few studies have been conducted to analyze sand-dust events in North China from the perspective of sand-dust processes. Although there are a few studies on the spatio-temporal variation characteristics of sand-dust processes, they are mainly based on outdated data or case studies of major sand-dust events. In this study, the evolution characteristics of sand-dust processes in China over the last 60 years are studied based on the identification method and several characteristic quantities (including duration and impact range) of sand-dust weather processes defined in the Operational Regulations of Monitoring and Evaluation for Regional Weather and Climate Processes newly issued by the China Meteorological Administration in 2019. First, through statistics, we obtain the annual occurrence frequency, annual days, and the annual number of affected stations of sand-dust processes (including sand-dust storms, blowing sand, and suspended dust) from January 1961 to May 2021. Based on the Mann–Kendall test (MK) and Ensemble Empirical Mode Decomposition (EEMD), we analyzed evolution trends and probability distribution characteristics of annual occurrence frequency, annual days, and the annual number of affected stations of sand-dust processes. In addition, we investigate the start time of the first and the last dust processes in each of the past 60 years, as well as the seasonal distribution characteristics of sand-dust processes. The results show that under the background of global warming, the sand-dust weather in China tends to decrease significantly. Specifically, the annual occurrence frequency and annual days showed an upward trend before the 1980s and a significant downward trend after that, as well as the significant turnarounds in the annual number of dust processes that occurred in the 1990s and around 2010. Moreover, the sand-dust processes tend to start later and end earlier. The sand-dust processes are mainly concentrated between March and May, with the highest occurrence probability in April.